Crime, inequality and public health: a survey of emerging trends in urban data science - Luca, Massimiliano; Campedelli, Gian Maria; Centellegher, Simone; Tizzoni, Michele; Lepri, Bruno (Frontiers in Big Data, 2023)
Urban agglomerations are constantly and rapidly evolving ecosystems, with globalization and increasing urbanization posing new challenges in sustainable urban development well summarized in the United Nations' Sustainable Development Goals (SDGs). The advent of the digital age generated by modern alternative data sources provides new tools to tackle these challenges with spatio-temporal scales that were previously unavailable with census statistics. In this review, we present how new digital data sources are employed to provide data-driven insights to study and track (i) urban crime and public safety; (ii) socioeconomic inequalities and segregation; and (iii) public health, with a particular focus on the city scale.